Regularities of elastic anisotropic strains caused by T-H-P influence on the structural transition and properties of magnetic semiconductors - Polyakov, P.I.; Kucherenko, S.S. (Functional Materials, 2004)
A generalizing analysis of experimental results on resistivity, magnetostriction, and phase transitions has been performed for magnetic semiconductors, namely, L₀.₇Ca₀.₃MnO₃ polycrystals and LaMnO₃ single crystals exposed to temperature (T), magnetic field (H), and hydrostatic pressure (P). The magneto-,baro-, and baromagnetoresis-tive effects have been revealed, where their maxima temperatures, Tpp, have been found to be constant and to coincide with the metal-semiconductor structural phase transition (PT) temperature, Tms. The "cooling" and "heating" effects of the magnetic field and pressure have been established, thus enabling to validate the regularities of Tms(H), Tms(P), and Hg(T) variations. The correspondence between T-H-P effect (5.1 К ~ 2.42 kOe ~ 1 kbar) on the resistivity properties and T-H effect (5.2 К-2.5 kOe) on the magnetostriction properties of the magnetic semiconductors has been estimated. The sign alternation has been revealed in variations of properties and effects as well as regularities of competing influence of thermo-, baro-, and magneto-elastic anisotropically straining (EAS) stresses. The positions of critical lines Tms(H), Tms(P), Hg(T) and points Tx, Px, PPX, Px', Tpp = Tms, T& have been defined, their correspondences in resistivity and magnetostriction behaviors has been established. Basing on the variety of critical lines and points, the correspondence and sign alternation of T-H-P influence through the mechanism of EAS stresses have been substantiated. Проведен обобщающий анализ экспериментальных результатов изменений резистив-ности, магнитострикции, фазовых переходов магнитных полупроводников: поликристаллического L₀.₇Ca₀.₃MnO₃ и монокристаллического LaMnO₃ под влиянием температуры (‘), магнитного поля (Н) и гидростатического давления (Р). Выявлены магнито-, баро- и баромагниторезистивный эффекты, в которых определено постоянство температуры Трр их максимумов, совпадающей с температурой Tms структурного фазового перехода "металл-полупроводник". Установлены "охлаждающий" и "нагревающий" эффекты магнитного поля и давления, позволяющие обосновать закономерности изменения Tms(H), Tms(P) и Hg(T). Получена оценка соответствий влияния T-H-P (5,1 К ~ 2,42 kOe ~ 1 kbar) на резистивные свойства, и влияния T-H (5,2 К-2,5 kOe) на магни-тострикционные свойства магнитных полупроводников. Выявлена знакопеременность в изменениях свойств, эффектов и закономерности конкурирующего влияния термо-, баро- и магнитоупругих анизотропно деформирующих (УАД) напряжений. Определены положения критических линий TmV(H), Tms(P), Hg(T)) и точек TX, PX, PPX, PX, TPP ~ T , T&. Установлены их соответствия на зависимостях изменений удельного сопротивления и магнитострикции. Из многообразия выделенных критических линий и точек установлено и дано обоснование значения оценок соответствий и знакопеременности влияния T-H-P через механизмы УАД напряжений. Виконано узагальнюючий аналіз експериментальних результати змін рєзистивності, магнітострикції, фазових переходів магнітних напівпровідників: полікристалічногоL₀.₇Ca₀.₃MnO₃ та монокристалічного LaMnOз під впливом температури (T), магнітного поля (H) та гідростатичного тиску (P). Виявлено магніто-, баро- та баромагніторезис-тивний ефекти, для яких визначено постійність температури Tpp їх максимумів, яка співпадає з температурою Tms структурного фазового переходу "метал-напівпровідник". Виявлено "охолоджувальний" та "нагрівальний" ефекти магнітного поля та тиску, які уможливлюють обгрунтування закономірності змін Tms(H), Tms(P) та Hg(T). Отримано оцінку відповідностей впливу T-H-P (5,1 K-2,42 kOe ~ 1 kbar) на резистивні властивості та впливу T-H (5,2 K-2,5 kOe) на магнітострикційні властивості магнітних напівпровідників. Виявлено знакозмінність у змінах властивостей, ефектів та закономірності конкурентного впливу термо-, баро- та магнітопружних анізотропно деформуючих (ПАД) напруг. Визначено положення критичних ліній Tms(H), Tms(P), Hg(T) та точок T;, P;, PP;, P;, Tpp = Tms, T&. Встановлено їх відповідності на залежностях змін питомого опору та магнітострикції. З різноманіття виділених критичних ліній та точок встановлено та обгрунтовано значення оцінок відповідностей та знакозмінності впливу T-H-P через механізми ПАД напруг.